Competitiveness of the Exports of the Mexican Chemical Sector in the United States of America and the European Union, 1994-2015 (2023)
The objective of this article is to analyze the evolution of the competitiveness of the exports of the Mexican chemical industry in the United States (U.S.) and European Union (E.U.) markets, by product category, between 1994 and 2015. For this, the structural transformations occurred in the specialization patterns of its competitors in each market are taking as a reference. The hypothesis that the change in the composition of exports does not occur in a dynamic sense is confirmed, as it does not occur towards products with a growing participation in world markets, nor is it registered in favor of the manufacture and sale of goods with higher degrees of sophistication. The finding results from the application of a dynamic shift-share technique that decomposes the variations over time of the differentials between Mexico's exports and those of its main competitors into three effects (structural, competitive and interactive).